Gender disparity in access to education, under-5 mortality, and economic growth in sub-Saharan Africa - Wang L.; Nwabuoku M.; Zhang J.; Osabohien R. (Women's Health and Action Research Centre, 2024)
This paper empirically analyses the impact of gender disparity in access to education and under 5 mortality on economic growth in selected sub-Saharan African (SSA) countries from the period 2005 2020. The study engaged a panel data of 17 selected SSA countries sourced from the World Development Indicators (WDI) and the United Nations Institute for Statistics (UNIS) and applied the instrumental variable generalised method of moments analytical approach. The result shows that the interaction between gender parity in access to education and primary school enrolment has a significant impact on economic growth. The study concludes that policies to promote gender parity in access to education would be of paramount importance to increase economic growth towards the actualisation of sustainable development goal related to inclusive and equitable quality education and the promotion of lifelong learning opportunities (SDG4) in SSA countries. 2023, Women's Health and Action Research Centre. All rights reserved.